Harvard business review on advancing your career. - Harvard Business Review Press (Boston, Mass. : Harvard Business Review Press, 2011)
If you need the best practices and ideas for achieving career growth and fulfillment-but don't have time to find them-this book is for you. Here are 11 inspiring and useful perspectives, all in one place.
How will you measure your life? -- Turn the job you have into the job you want -- How to stay stuck in the wrong career -- Job-hopping to the top and other career fallacies -- Are you a high potential? -- Why you didn't get that promotion -- Why men still get more promotions than women -- Five ways to bungle a job change -- The right way to be fired -- How to protect your job in a recession -- How leaders create and use networks.
Includes index.
Description based on print version record.
Keywords: Career development; Promotions; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Reference; BUSINESS & ECONOMICS / Skills; elektronické knihy; electronic books